Effect of etanercept concentration on human islet integrity - Acreman, S; Brandhorst, H; Abraham, A; Johnson, P; Brandhorst, D (Elsevier, 2017)
Etanercept is widely used as an antiinflammatory drug to improve engraftment after intraportal islet transplantation. In contrast to other immunosuppressive agents, very little is known about detrimental effects of etanercept on islets. The aim of this pilot study was to define the toxic range of etanercept.Human islets isolated from 8 donors were cultured for 4-5 days at 37°C in culture medium supplemented with etanercept at concentrations from 2.5 to 40 μg/mL, corresponding to potential in vivo levels within the portal vein. After culture, islet equivalent (IEQ) yield, fragmentation index (islet number/IEQ), purity, viability, and stimulated insulin release (2 vs 20 mmol/L) were assessed and normalized to islets before culture.Yield (73 ± 8%) and viability (91 ± 4%) were highest with 5 μg/mL etanercept. Islet loss was evident when etanercept was ≥10 μg/mL (55 ± 7%; P < .05 vs control). Fragmentation (154 ± 34%; P < .05) was markedly increased and viability (81 ± 4%, P < .05) markedly decreased with etanercept >10 μg/mL. The accumulation of cell debris at concentrations ≥20 μg/mL resulted in a significant reduction of islet purity (84 ± 3%; P < .05). Etanercept did not interfere with stimulated insulin secretion at concentrations ≤10 μg/mL. The maximum stimulation index was noted at 2.5 μg/mL (1.8 ± 0.1).Etanercept is tolerated by isolated human islets at concentrations <10 μg/mL. Our data suggest that the tight range between benefit and toxicity should be considered for dosage and administration of etanercept.